Matrix-assisted laser desorption ionization mass spectrometry based quantitative analysis of cordycepin from Cordyceps militaris - Jian Chen; Hai-Fang Li; Guozhu Zhao; Jin-Ming Lin; Xiangwei He (Elsevier, 2021)
Cordycepin, which has great immunomodulatory activities such as anticancer, antifungal, antivirus, antileukemia and lipid-lowering ones, is the secondary metabolite of Cordyceps militaris (C. militaris). Liquid submerged fermentation is the common cultivation process to produce cordycepin. To optimize the fermentation process and improve production, monitoring the cordycepin secretion in the fermentation is essential. The measurement based on chromatography-mass spectrometry methods is generally involved in the complex sample pretreatments and time-consuming separation, so more rapid and convenient methods are required. Matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) is more attractive for faster and direct detection. Therefore, MALDI-MS detection combined with isotope-labeled internal standard was applied to the measurement of cordycepin content in the fermentation broth and mycelium. This method made accurate quantification of cordycepin in the range of 5-400 μg/mL with a relative standard deviation of 5.6%. The recovery rates of fermentation samples after the 1, 13, and 25 days were 90.15%, 94.27%, and 95.06%, respectively. The contents of cordycepin in the mycelium and fermentation broth were 136 mg/g and 148.39 mg/mL on the 20th culture day, respectively. The cordycepin secretion curve of the liquid fermentation of C. militaris was real-time traced over 25 days.